Screen Time Practices among Children Visiting Pediatric Clinic: A Study of Parental Perception and Practices - Dahal, Sonia; Pyakurel, Kumud (Annapurna Journal of Health Sciences, 2026)
Introduction: With the increasing prevalence of digital devices, children’s screen time has significantly risen, raising concerns about its impact on their physical, mental, and social development. Parental perception and practices play a crucial role in shaping children’s media use and mitigating potential adverse effects. This study aimed to assess parental perceptions, screen time management practices, and the screen time behaviors of children attending a pediatric clinic. Methods: A descriptive cross-sectional study was conducted over nine months (July 2024–March 2025) at Birat Medical College Teaching Hospital. A structured, self-administered questionnaire was completed by 413 parents or guardians of children aged 2–12 years visiting the pediatric outpatient clinic. Data were analyzed using SPSS software and descriptive statistics, including frequencies and percentages, were used for analysis. Results: Most children (73.6%) had screen exposure exceeding one hour daily, with smartphones being the most commonly used device (71.2%). Watching videos (61.3%) was the dominant activity. Nearly 80% of parents reported setting screen time rules for their children, and 71% expressed concern regarding its impact. Educational benefits (63.7%) and creativity (36.6%) were recognized, yet many parents also cited adverse effects on emotional well-being (52.3%) and sleep (38.3%). Parental screen habits were closely aligned with children’s usage patterns. Despite confidence in managing screen use (79.7%), over 30% of parents occasionally sought guidance on healthier practices. Conclusion: Children’s screen time remains substantial, with both positive and negative parental perceptions. While many parents demonstrate awareness and attempt regulation, gaps persist in aligning practices with recommendations. Targeted interventions and parental education are essential to foster balanced screen time habits and mitigate potential harms.